Purong Pinoy the cultural identity of Filipino-foreign youth as manifested by their communication practices - Alberto, Francesca Maria C.; Favila, Alberto Mecel Faith A.; Pernia, Elena E. (2012)
"This thesis examines how the socio-demographic characteristics, foreign and Filipino affiliation, and parents' cultural value context affect the cultural communication practices of Fil-foreign youth aged 19 to 24. Communication plays a vital role in the negotiation and construction of an individual's cultural identity as he/she interacts with others, and at the same is also the most common method of expressing his/her cultural identity. Data were gathered by means of 10 self-administered questionnaires with in-depth focus interviews of Fil-foreign informants coming from different racial backgrounds. Analyzed and Illustrated further by using Hofstede's cultural dimensions (2011) as guide, data shows that the Fil-foreign informants chose the language they are going to use by assessing the current situation and the other person's ability to speak a particular language. In addition, their cultural identity is greatly influenced by affiliation and familiarity to both of their Filipino and foreign cultures. Language was considered an indicator of their cultural identity, and Filipino was used to evoke their Filipino roots."
Vita.
Undergraduate thesis (A.B. Communication Research)--University of the Philippines.
Keywords: Communication and culture -- Philippines